2021
DOI: 10.1002/ab.21947
|View full text |Cite
|
Sign up to set email alerts
|

HEXACO personality correlates of adolescents' involvement in bullying situations

Abstract: Adolescents' involvement in bullying situations is—at least partially—personality trait‐activated. Although some studies investigated personality correlates of bullying and being victimized, little is known about personality correlates of bystander responses (i.e., reinforcing, outsider behavior, indirect defending, and direct defending). The present study investigated whether Dutch adolescents' self‐reported HEXACO personality traits could explain their peer‐reported involvement in bullying (N = 552; Mage = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Alsheikh Ali, 2020;Chabrol et al, 2015;Lau & Marsee, 2013;Muris et al, 2013;Pabian et al, 2015;Sijtsema et al, 2019;Van Geel et al, 2017;Wright et al, 2020;Zhang & Zhao, 2020), while higher levels of benevolent characteristics such as fairness, sincerity, modesty, and lack of greed were associated with lower symptom levels of these externalizing disorders (cf. Allgaier et al, 2015;Book et al, 2012;Farrell & Volk, 2017;Geng et al, 2021;MacDonell & Willoughby, 2020;Pronk et al, 2021). These results were as anticipated and fully in keeping with what has been documented in adult populations (see for reviews: Ashton et al, 2014;Muris et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Alsheikh Ali, 2020;Chabrol et al, 2015;Lau & Marsee, 2013;Muris et al, 2013;Pabian et al, 2015;Sijtsema et al, 2019;Van Geel et al, 2017;Wright et al, 2020;Zhang & Zhao, 2020), while higher levels of benevolent characteristics such as fairness, sincerity, modesty, and lack of greed were associated with lower symptom levels of these externalizing disorders (cf. Allgaier et al, 2015;Book et al, 2012;Farrell & Volk, 2017;Geng et al, 2021;MacDonell & Willoughby, 2020;Pronk et al, 2021). These results were as anticipated and fully in keeping with what has been documented in adult populations (see for reviews: Ashton et al, 2014;Muris et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…A number of studies can be found exploring the relations between this personality factor (and the other HEXACO traits) and types of externalizing problem behavior. It was found that honesty-humility was negatively correlated with (cyber)bullying (Book et al, 2012;Farrell & Volk, 2017;Geng et al, 2021;Pronk et al, 2021), aggression (MacDonell & Willoughby, 2020, and antisocial behavior in general (Allgaier et al, 2015). Further, in most studies, the influence of honesty-humility on externalizing problems remained statistically significant when controlling for the other HEXACO traits (Book et al, 2012;Farrell & Volk, 2017;Pronk et al, 2021), with agreeableness sometimes also making a significant negative contribution.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This fact suggests that extraversion contributes to the initiation of bullying among adolescents, as extroverts exhibit increased activity and this often leads them to behave recklessly, ignoring the potential for serious consequences or the threat of punishment (Bjornebekk, 2007). Connolly and O'More (2003) also found that aggressors exhibited higher levels of psychoticism, extraversion, and neuroticism than those who did not participate in bullying and, on the other hand, being victimized was positively related to emotionality and negatively to extraversion (Pronk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits like honesty-humility, emotionality, agreeableness, and openness to experience were negatively related to bullying perpetration (Pronk et al, 2021). However, different results have appeared while studying different populations.…”
Section: Bullying and Personality (The Dark Tetrad Traits)mentioning
confidence: 99%